Trendi na področju kadrovskega managementa (University of Maribor Press, 2024)
The monograph presents trends in various areas of human resource management. The first chapter focuses on an overview of the key technological trends in the HR function in telework. The second chapter examines difficult conversations in the workplace and how individuals deal with them. In the third chapter, competencies for managing complex crises are presented. The fourth chapter deals with blockchain technology in the field of HR management. The fifth chapter presents a systematic review of green competencies in healthcare. The sixth chapter takes us through the employee evaluation and reward system design. The last, seventh chapter points out the importance of prenatal education and its impact on the quality of life after childbirth and the development of the individual.